Proceedings of the Eleventh International Conference on World Wide Web - WWW '02 2002
DOI: 10.1145/511511.511514
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of HITS-based algorithms on web documents

Abstract: In this paper, we present t wo w ays to improve the precision of HITS-based algorithms on Web documents. First, by analyzing the limitations of current HITS-based algorithms, we propose a new weighted HITS-based method that assigns appropriate weights to in-links of root documents. Then, we combine content analysis with HITS-based algorithms and study the e ects of four representative r e l e v ance scoring methods, VSM, Okapi, TLS, and CDR, using a set of broad topic queries. Our experimental results show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 2 publications
(2 reference statements)
0
24
0
Order By: Relevance
“…As for the page ranking, PageRank [11] , HITS [12], or other classical ranking algorithms can be used to rank the pages by the degree of relevance with the retrieval keywords, ensuring that users can get the information they need as quickly as possible.…”
Section: A the Organization Of Search Resultsmentioning
confidence: 99%
“…As for the page ranking, PageRank [11] , HITS [12], or other classical ranking algorithms can be used to rank the pages by the degree of relevance with the retrieval keywords, ensuring that users can get the information they need as quickly as possible.…”
Section: A the Organization Of Search Resultsmentioning
confidence: 99%
“…Li et al [22] found that HITS is vulnerable to the "small-in-large-out" situation. Gyongyi et al describe a new algorithm, TrustRank, to combat Web spam [17].…”
Section: Related Workmentioning
confidence: 99%
“…However with the appearance of link farms, in which sites are densely interconnected, HITS is no longer robust [5,21,22,8]. 1 For example, the top 10 authorities generated by HITS for query weather are shown in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…Methods based on mutual reinforcement principle have been widely reported in literature especially in the domains of journal evaluation and more recently on Web search [4,14,17,21,13].…”
Section: Related Work Using Mutual Reinforcementmentioning
confidence: 99%
“…Google's pagerank of a particular Web-page is a measure of its standing based on its link structure [4]. In [17], modification of HITS by assigning a weight to each link based on textual similarities between pages has been found to perform better than the original HITS.…”
Section: Related Work Using Mutual Reinforcementmentioning
confidence: 99%